2022
DOI: 10.3390/antibiotics11101379
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs of Tigecycline Resistance in Acinetobacter baumannii and the Resistance Mechanism Revealed by a Transposon Mutation Library

Abstract: Acinetobacter baumannii is one of the main pathogens causing nosocomial and community-acquired infections. Tigecycline is an important antibiotic for the treatment of multidrug-resistant A. baumannii infections, but strains resistant to tigecycline have also emerged. There are still many unclear questions concerning the mechanism of tigecycline resistance in A. baumannii. In this study, tigecycline-susceptible and tigecycline-intermediate strains were gradually cultured with sub-minimum inhibitory concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Both the CUS (chaperon-usher secretion) operator system and the surface antigen protein A are related to the formation of biofilms [35,36]. In this study, these biofilm formation-related proteins CsuA/B, CsuC, CsuE were all up-regulated in 17978R, but down-regulated in A54R, which was consistent with the results of the biofilm-forming ability of the two strains [37]. The relationship between the biofilm-forming ability and antibiotic resistance is still controversial.…”
Section: Discussionsupporting
confidence: 90%
“…Both the CUS (chaperon-usher secretion) operator system and the surface antigen protein A are related to the formation of biofilms [35,36]. In this study, these biofilm formation-related proteins CsuA/B, CsuC, CsuE were all up-regulated in 17978R, but down-regulated in A54R, which was consistent with the results of the biofilm-forming ability of the two strains [37]. The relationship between the biofilm-forming ability and antibiotic resistance is still controversial.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, the presence of multi-drug resistant (MDR) pathogens raises a noteworthy concern. MDR strains often occurring in intensive care units have shown an alarming mortality rate due to the difficulty of treatment with antibiotics ( Wang P. et al., 2022 ). According to susceptibility levels in the Asia-Western Pacific region, tigecycline treatment is currently effective in most MDR infections ( Li et al., 2015 ).…”
Section: Enterobacteralesmentioning
confidence: 99%
“…Notably mcr-1 plasmids can act as helper plasmids, potentially enhancing the chance of dissemination of plasmid-mediated tigecycline resistance ( Sun J. et al., 2019 ). Various studies revealed the spread of genes through HGT ( Wang P. et al., 2022 ). Tet genes can be found in plasmids harboring IncQ1.…”
Section: The History and Origin Of The Tet -Genes ...mentioning
confidence: 99%